Putting prospection into practice: Methodological considerations in the use of episodic future thinking to reduce delay discounting and maladaptive health behaviors - Jeremiah Michael Brown; Jeremiah Michael Brown; Jeffrey Scott Stein; Jeffrey Scott Stein (Frontiers Media S.A., 2022)
In recent years, episodic future thinking (EFT) has emerged as a promising behavioral intervention to reduce delay discounting or maladaptive health behaviors; however, considerable methodological heterogeneity in methods for eliciting engagement in EFT has been observed in prior research. In this narrative review, we briefly describe methods for generating EFT cues, the content of EFT cues, common control conditions for experiments utilizing EFT, and considerations for cue delivery and implementation. Where possible, we make suggestions for current best practices in each category while identifying gaps in knowledge and potential areas of future research. Finally, we conclude by using the NIH Stage model to better frame the current state of the literature on EFT and propose gaps to be addressed if EFT is to be both an efficacious and effective behavioral intervention.